Assessing the Current Status of Vietnam's Coffee Exports in the Period 2014-2023 in the Global Coffee Value Chain - Nguyen, Trung Le; Do, Phuc Bao Nguyen; Nguyen, Lan Hoang; Bui, Thai Huy (Darul Yasin Al Sys, 2024)
Vietnam has favorable geographical location and weather to grow and develop robusta coffee varieties. Vietnam's production area is more than 95% of robusta coffee output out of a total planting area of 600,000 hectares. In 2022, coffee productivity will reach about 28.2 tons/1 hectare, reaching the highest level since 2005, according to Department of Crop Production data. The robusta coffee variety in Vietnam is also considered the best coffee variety in the world. Therefore, according to statistics from the Vietnam Commodity Exchange, in 2023, Vietnam will be the country with the world's highest robusta coffee export value, accounting for 36% of the total global coffee export value, followed second by Brazil with 28%. In 2021, Vietnam ranks 5th globally, with coffee exports reaching 2.35 billion USD. In 2022, Vietnam exported 1.68 million tons of coffee, but the turnover reached only about 3.9 billion USD. Of these, 82% of Vietnam's coffee is exported raw (mainly Robusta), valued at 2.9 billion USD. In contrast, the export turnover of Arabica coffee is only 260 million USD for decaffeinated coffee. 76.9 million USD and roasted, ground-illat coffee worth 598 million USD. Colombia and Switzerland have a small amount of coffee exported, but the value is high thanks to the quality and coffee brands that the country has built. Vietnam's coffee exports set a new record with a turnover of 4.24 billion USD in 2023. Just past the beginning of the new year, Robusta coffee prices continue to record many new peaks. With this advantage, the coffee industry has a solid foundation for its export goal in 2024.